1964
DOI: 10.1128/jb.88.4.850-857.1964
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF PHOSPHATE ION AND 2,4-DINITROPHENOL ON THE ACTIVITY OF INTACT CELLS OF THIOBACILLUS FERROOXIDANS

Abstract: Utah), AND FRED M. SHAFIA. Effect of phosphate ion and 2,4-dinitrophenol on the activity of cell suspensions of Thiobacillus ferroo tidans. J. Bacteriol. 88:850-857. 1964.-The rate of oxidation of ferrous salts or elemental sulfur by aged cell suspensions, phosphate-depleted cells, or 2,4-dinitrophenol (DNP)-treated cells of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…This is not surprising, since it is known that a substantial amount of ATP is used by T. ferrooxidans for CO 2 fixation [20]. These results support the previous observations regarding a lower bioleaching activity for T. ferrooxidans in the absence of phosphate [9,10].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is not surprising, since it is known that a substantial amount of ATP is used by T. ferrooxidans for CO 2 fixation [20]. These results support the previous observations regarding a lower bioleaching activity for T. ferrooxidans in the absence of phosphate [9,10].…”
Section: Resultssupporting
confidence: 90%
“…Phosphate ion (Pi) is an essential nutrient for all living organisms. Therefore, the lack of phosphorus may be a stressing condition which can affect the bioleaching of minerals [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This higher efficiency corresponds t o about 4.5 millimoles CO, fixed per mole of Fe2+ oxidized, corresponding t o 54 mg C0,-carbon or a dry weight yield (50% carbon) of 108 mg bacteria. BECK and SHAFIA (1964) obtained growth yields of 100 mg dry wt per mole FeSO,, indicating comparable efficiencies of GO,-fixation t o operate during growth. I n cultures exposed t o normal air, the amounts of 0, and CO, dissolved a t 30 "C may be calculated for pure water as the product of the BUNSEN absorption coefficient and actual volume percentage of each gas present.…”
mentioning
confidence: 77%
“…It is thus not necessary to invoke special adaptation in these organisms to enable them t o survive in conditions of low dissolved CO,, for although dissolved (30:and HCO, will be a t very low levels, they must be formed immediately when dissolved CO, enters the cell cytoplasm, which is a t the more nearly neutral pH a t which the enzymes are known t o function (GALE and BECK 1967). BECK and SHAFIA (1964) demonstrated that C0,-fixation by non-growing T . ferrooxidans a t pH 2.7 was markedly affected by the partial pressure of CO, in WAR-BURG flasks, such that 0.7 ymoles CO, were fixed per 100 ymoles 0, consumed with ea.…”
mentioning
confidence: 99%
“…Reducing power required is supplied through energy-requiring reversed electron flow [6][7][8]. The oxidation of ferrous iron is the only energy-generating step in the growth of the organism, but instead of being stimulated by uncouplers as in mitochondria it is actually inhibited by uncouplers [9]. The oxidation is also inhibited by permeant anions and weak acids which dissipate Dp by affecting Dw and DpH [10][11][12].…”
Section: Introductionmentioning
confidence: 99%